2013
DOI: 10.1242/jeb.093146
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of marine mammal tracheas

Abstract: In 1940, Scholander suggested that stiffened upper airways remained open and received air from highly compressible alveoli during marine mammal diving. There are few data available on the structural and functional adaptations of the marine mammal respiratory system. The aim of this research was to investigate the anatomical (gross) and structural (compliance) characteristics of excised marine mammal tracheas. Here, we defined different types of tracheal structures, categorizing pinniped tracheas by varying deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 47 publications
7
62
0
Order By: Relevance
“…However, these differences in the terminal airways did not result in a marked difference in the pressure-related pulmonary shunt during forced dives in a pressure chamber (Kooyman and Sinnett, 1982). One explanation may be the significant variation in compliance estimates of the upper airways between species (Bagnoli et al, 2011;Davenport et al, 2013;Moore et al, 2014). A comparative study showed that deep-diving pinnipeds have a more compliant trachea as compared with more shallow-diving species whereas deep-diving cetaceans have a stiffer trachea than shallow-diving cetaceans .…”
Section: Airway Compliancementioning
confidence: 98%
See 3 more Smart Citations
“…However, these differences in the terminal airways did not result in a marked difference in the pressure-related pulmonary shunt during forced dives in a pressure chamber (Kooyman and Sinnett, 1982). One explanation may be the significant variation in compliance estimates of the upper airways between species (Bagnoli et al, 2011;Davenport et al, 2013;Moore et al, 2014). A comparative study showed that deep-diving pinnipeds have a more compliant trachea as compared with more shallow-diving species whereas deep-diving cetaceans have a stiffer trachea than shallow-diving cetaceans .…”
Section: Airway Compliancementioning
confidence: 98%
“…The relationship between estimated total lung capacity (TLC est ; broken line, Kooyman, 1973) and M b for marine mammals reveals that the volume of most breaths of marine mammals is not close to the vital capacity of the animal. References: bottlenose dolphin (Fahlman et al, 2015b), gray seal (Reed et al, 1994), Weddell seal (Kooyman et al, 1971), harbor porpoise (Reed et al, 2000), California sea lion (Kerem et al, 1975;Matthews, 1977), pilot whale (Olsen et al, 1969), killer whale (Spencer et al, 1967;Kasting et al, 1989), beluga whale (Kasting et al, 1989;Epple et al, 2015), walrus (Fahlman et al, 2015a), Patagonia sea lion (Fahlman and Madigan, 2016) Denison and Kooyman, 1973;Kooyman, 1973;Tarasoff and Kooyman, 1973;Leith, 1976;Kooyman and Sinnett, 1979;Kooyman and Cornell, 1981;Fahlman et al, 2011Fahlman et al, , 2014Fahlman et al, , 2015bMoore et al, 2011Moore et al, , 2014. Studies using trained marine mammals that voluntarily participate have been used to define flowvolume characteristics (Olsen et al, 1969;Kooyman and Cornell, 1981;Fahlman et al, 2015b;Fahlman and Madigan, 2016).…”
Section: Respiratory Mechanics: Flow and Compliancementioning
confidence: 99%
See 2 more Smart Citations
“…Despite the value of these theoretical studies, the results should be interpreted with caution, as the current understanding of how gas exchange is affected by compression of the respiratory system is rudimentary at best. Recent studies suggest that there is considerable structural (anatomical) and functional (compliance) variability in the upper and lower airways of different orders, families and species of marine mammals (Moore et al, 2014;Piscitelli et al, 2010Piscitelli et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%